Proteostasis in Cerebral Small Vessel Disease - Haffner, Christof (Frontiers in Neuroscience, 2019)
Maintaining the homeostasis of proteins (proteostasis) by controlling their synthesis, folding and degradation is a central task of cells and tissues. The gradual decline of the capacity of the various proteostasis machineries, frequently in combination with their overload through mutated, aggregation-prone proteins, is increasingly recognized as an important catalyst of age-dependent pathologies in the brain, most prominently neurodegenerative disorders. A dysfunctional proteostasis might also contribute to neurovascular disease as indicated by the occurrence of excessive protein accumulation or massive extracellular matrix expansion within vessel walls in conditions such as cerebral small vessel disease, a major cause of ischemic stroke, and cerebral amyloid angiopathy. Recent advances in brain vessel isolation techniques and mass spectrometry methodology have facilitated the analysis of cerebrovascular proteomes and fueled efforts to determine the proteomic signatures associated with neurovascular disease. In several studies in humans and mice considerable differences between healthy and diseased vessel proteomes were observed emphasizing the critical contribution of an impaired proteostasis to disease pathogenesis. These findings highlight the important role of a balanced proteostasis for cerebrovascular health.